Socialization Of Digital-Based Msme Accounting Skills Improvement In Improving The Quality Of Msme Financial Management - Sasongko, Restu Widyo; Widiniarsih, Dewi Mariam; Sevtiana, Agus; Bakri, Asri Ady; Said, Saida (Journal Of Human And Education (JAHE), 2024)
This socialization began with complaints from MSME stakeholders when the author did community service in the villages mentioned for a period of one to two months. Because the authors gathered here are members of a group of lecturers throughout Indonesia, the authors often exchange opinions about the problems faced when doing community service. Coincidentally, within a period of time that is not much different, the authors encountered the same problem and carried out activities in the same form separately, namely in Bojongmalaka Village, West Java, Menanti Village, Lampung, and Butung Village, Makassar. The devotee hopes that the financial management problems experienced by MSME stakeholders can be resolved soon and hopefully the author's socialization regarding financial management can help MSME stakeholders in solving their problems.